Mencerahkan Zaman: Ideologi dan Gerakan Muhammadiyah dalam Mewujudkan Masyarakat Islam yang Berkemajuan - Mohadib, Mohadib; Tajudin, Tajudin (MISYKAT AL-ANWAR JURNAL KAJIAN ISLAM DAN MASYARAKAT, 2024)
Muhammadiyah, as one of the leading Islamic movements in Indonesia, possesses a strong ideology that serves as a guide in realizing an ideal Islamic society. This ideology, rooted in the thoughts of KH Ahmad Dahlan, responded to the social and colonial conditions of the Dutch era. Muhammadiyah emphasizes the purification and simplification of Islam, as well as the integration of Islamic values with local culture. This is done to maintain the relevance of Islamic teachings to the contemporary context. The ideology not only serves as a guide but also an inherent identity element within the movement, directing actions and decisions towards achieving shared goals. Muhammadiyah is known as a moderate Islamic movement that is open to differences and strives to renew and purify the understanding and practice of Islam according to the context of the times. This research employs a descriptive qualitative methodology to analyze Muhammadiyah's ideology and its implementation in realizing an ideal Islamic society.